Role of the playground environment on levels of physical activity in elementary school children - Schaefer, Christine Adele, author; Browning, Raymond C., advisor; Nelson, Tracy L., committee member; Peel, Jennifer L., committee member (Colorado State University. Libraries, 2011)
The school environment offers opportunities for children to be active, particularly during recess periods. Yet the influence of the playground on levels of physical activity (PA) throughout the day has not been well described. PURPOSE: The purpose of this study was to determine the role of renovated (Learning Landscapes, LL) vs. non-renovated playgrounds on levels of recess, school day and after school PA in elementary school children. The data collected serve as baseline for the Intervention of PhysicaL Activity in Youth (IPLAY) Study. METHODS: We measured height, weight and 5-6 days of free-living PA via wrist-mounted Actical accelerometers in 277 elementary school children. These students were enrolled in schools serving low socioeconomic status (SES) families (76.9% receiving free and reduced lunch) in metropolitan Denver, CO. Overweight status was defined as ≥ 85th percentile BMI-for-age. We applied age and wrist-specific cutpoints to the data to determine total number of minutes and percent of time spent in moderate-vigorous PA (MVPA). Univariate ANOVA was conducted to determine between-subject effects of weight status, presence of LL and sex on recess, school day and after school PA. RESULTS: During recess and the school day, but not after school, children in LL accumulated more PA than their non-LL counterparts. Boys were significantly more active than girls at all time points. Normal weight children were more active than overweight children over the course of the whole school day. Children in LL were no more likely than their non-LL counterparts to meet the guideline for daily MVPA. CONCLUSIONS: These data demonstrate that in LL schools, normal weight girls and all boys participate in greater levels of recess PA compared to their non-LL counterparts. However, overweight girls¡¯ levels of PA are not different between playground conditions, signifying the need for additional approaches to encourage them to be more active. Although more active during recess, children in LL are no more likely than non-LL children to meet the guideline for PA, indicating that recess duration may be an important factor in daily PA accumulation.
Keywords: accelerometer; playground; physical activity; intervention; children